1998
DOI: 10.1097/00001756-199808030-00016
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I enhances survival of embryonic chick ciliary ganglion neurons in a calcium-dependent way

Abstract: We have shown that neurons from embryonic chick ciliary ganglia in primary culture possess receptors for insulin-like growth factor I (IGF-I). When added to serum- and insulin-free culture medium, the factor potently enhanced neuronal survival as observed after 24 and 48 h of culture. The effect saturated at 5 ng/ml. Laminin was not necessary for the trophic effects of IGF-I; in the absence of the factor, it had no effect on neuronal survival. Insulin exerted a trophic effect similar to that observed with IGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Two hours after plating, neurons were clearly distinguishable from nonneuronal cells by their phase‐bright, rounded cell bodies and short processes. We have previously shown that all birefringent, round cells display electrophysiological properties of differentiated neurons (Distasi et al, 1998) and are positive for neuronal markers (Barale et al, 1998). Each experiment was made in duplicate; three or four independent experiments were performed for each individual treatment.…”
Section: Methodsmentioning
confidence: 97%
“…Two hours after plating, neurons were clearly distinguishable from nonneuronal cells by their phase‐bright, rounded cell bodies and short processes. We have previously shown that all birefringent, round cells display electrophysiological properties of differentiated neurons (Distasi et al, 1998) and are positive for neuronal markers (Barale et al, 1998). Each experiment was made in duplicate; three or four independent experiments were performed for each individual treatment.…”
Section: Methodsmentioning
confidence: 97%
“…In several mice model of ASD, IGF-II has been suggested as a potential novel therapeutic target for ASD [10]. IGFs have been shown to play important role in the survival of neurons [11]. Many studies in both animal and human ASD models have proven IGF1 as one of the most promising ASD therapeutic interventions to date.…”
Section: Introductionmentioning
confidence: 99%